Experimental study on the membrane electrode assembly of a proton exchange membrane fuel cell: effects of microporous layer, membrane thickness and gas diffusion layer hydrophobic treatment - Rui B. Ferreira (2017)
In this study, electrochemical impedance spectroscopy (EIS) is employed to analyze the influence of microporous layer (MPL), membrane thickness and gas diffusion layer (GDL) hydrophobic treatment in the performance of a proton exchange membrane (PEM) fuel cell. Results show that adding a MPL increases cell performance at low to medium current densities. Because lower ohmic losses are observed when applying a MPL, such improvement is attributed to a better hydration state of the membrane. The MPL creates a pressure barrier for water produced at the cathode, forcing it to travel to the anode side, therefore increasing the water content in the membrane. However, at high currents, this same phenomenon seems to have intensified liquid water flooding in the anode gas channels, increasing mass transfer losses and reducing the cell performance. Decreasing membrane thickness results into considerably higher performances, due to a decrease in ohmic resistance. Moreover, at low air humidity operation, a rapid recovery from dehydration is observed when a thinner membrane is employed. The GDL hydrophobic treatment significantly improves the cell performance. Untreated GDLs appear to act as water-traps that not only hamper reactants transport to the reactive sites but also impede the proper humidification of the cell. From the different designs tested, the highest maximum power density is obtained from that containing a MPL, a thinner membrane and treated GDL5.